The Israeli Arabic-speaking Facebook Pages And Its Effects On The Elements Of Palestinian National Identity - Ihab Ahmed Awais; Abeer Z. Alhossary; Ab Rahman, Z; Norhayati Rafida Abdul Rahim (Universidad Tecnica de Manabi, 2024)
nternational Journal of Health Sciences,6(S4), 8819–8843.